2016
DOI: 10.1039/c6nr07480d
|View full text |Cite
|
Sign up to set email alerts
|

The structural and electronic properties of NbSin−/0(n = 3–12) clusters: anion photoelectron spectroscopy and ab initio calculations

Abstract: Niobium-doped silicon clusters, NbSi (n = 3-12), were generated by laser vaporization and investigated by anion photoelectron spectroscopy. The structures and electronic properties of NbSi anions and their neutral counterparts were investigated with ab initio calculations and compared with the experimental results. It is found that the Nb atom in NbSi prefers to occupy the high coordination sites to form more Nb-Si bonds. The most stable structures of NbSi are all exohedral structures with the Nb atom face-cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 59 publications
7
42
0
Order By: Relevance
“…The experimental VDE and ADE of OTaC 2 – are obtained to be 2.85 ± 0.08 and 2.58 ± 0.08 eV, respectively. The measured details of experimental VDEs and ADEs can be found elsewhere …”
Section: Resultssupporting
confidence: 83%
“…The experimental VDE and ADE of OTaC 2 – are obtained to be 2.85 ± 0.08 and 2.58 ± 0.08 eV, respectively. The measured details of experimental VDEs and ADEs can be found elsewhere …”
Section: Resultssupporting
confidence: 83%
“…The HOMOs are all doubly occupied, and the LUMO is higher in energy than the HOMO by 3.27 eV, although the previous investigations have revealed that the HOMO-LUMO gap calculated with the B3LYP functional is more overestimate than that obtained from the other functional (BP86) by ∼1.00 eV. [67][68][69] This indicates that the BSi 11 − anion has a shell-closed electronic structure with a large HOMO-LUMO gap. The HOMO is a Si-Si σ orbital with bonding characters, mainly composed by the 3p orbitals of Si atoms.…”
Section: Bsi 12mentioning
confidence: 89%
“…The previous photoelectron spectroscopy and photoelectron imaging experiments combined with theoretical calculations suggested that the ground-state structures of Si 5 2– , Si 5 – , and Si 5 clusters are trigonal bipyramid with D 3h symmetry, and Si 5 five-membered ring geometric structure is not stable. Interestingly, here, we found that the Si 5 five-membered rings can be stabilized by the B atoms, thus, 10 Si atoms are able to form two Si 5 rings to encapsulate the B atoms in B 2 Si 10 –/0 . It is also interesting to note that two Si 6 six-membered rings can sandwich a transition metal atom such as Cr, V, or Nb, to form a hexagonal prism or distorted hexagonal prism structures. Although two Si 5 five-membered rings are able to sandwich a B 2 unit in B 2 Si 10 –/0 , the sandwich of B 2 by two Si 6 six-membered rings in B 2 Si 12 –/0 is not stable. This indicates that the B 2 unit is capable to stabilize the Si 5 rings rather than the Si 6 rings.…”
Section: Discussionmentioning
confidence: 99%